A revision of the Neotropical genus Austrohahnia Mello-Leitão (Araneae, Hahniidae) - Rubio, Gonzalo D.; Lo-Man-Hung, Nancy F.; Iuri, Hernán A. (Zootaxa, 2014)
The Neotropical genus Austrohahnia Mello-Leitão, 1942 is revised, comprising four species from Argentina. The genus is here transferred to the subfamily Hahniinae Bertkau, 1878 from Cybaeolinae Lehtinen, 1967. Austrohahnia is diagnosed by a single synapomorphy, short setae ventrally on the abdomen, in immature as well as adult stages. The type species A. praestans Mello-Leitão, 1942 is redescribed. Austrohahnia catleyi new species is described and illustrated based both sexes from the alder forests of northwestern Argentina. Austrohahnia melloleitaoi (Schiapelli & Gerschman, 1942) new combination was transferred from Hahnia C.L. Koch, 1841, the male is described and illustrated for the first time, and the female is redescribed. Austrohahnia isophthalma (Mello-Leitão, 1941) new combination is also transferred from Hahnia and considered a nomen dubium. New geographic records of studied species are provided.